Fabrication of Orange Fluorescent Boron-Doped Graphene Quantum Dots for Al3+ Ion Detection - Weitao Li; Luoman Zhang; Ningjia Jiang; Yongqian Chen; Jie Gao; Jihang Zhang; Baoshuo Yang; Jialin Liu (Molecules, 2022)
Aluminum is a kind of metal that we often encounter. It can also be absorbed by the human body invisibly and will affect our bodies to a certain extent, e.g., by causing symptoms associated with Alzheimer’s disease. Therefore, the detection of aluminum is particularly important. The methods to detect metal ions include precipitation methods and electrochemical methods, which are cumbersome and costly. Fluorescence detection is a fast and sensitive method with a low cost and non-toxicity. Traditional fluorescent nanomaterials have a high cost, high toxicity, and cause harm to the human body. Graphene quantum dots are a new type of fluorescent nanomaterials with a low cost and non-toxicity that can compensate for the defects of traditional fluorescent nanomaterials. In this paper, c-GQDs and o-GQDs with good performance were prepared by a bottom-up hydrothermal method using o-phenylenediamine as a precursor and citric acid or boric acid as modulators. They have very good optical properties: o-GQDs exhibit orange fluorescence under UV irradiation, while c-GQDs exhibits cyan fluorescence. Then, different metal ions were used for ion detection, and it was found that Al3+ had a good quenching effect on the fluorescence of the o-GQDs. The reason for this phenomenon may be related to the strong binding of Al3+ ions to the N and O functional groups of the o-GQDs and the rapid chelation kinetics. During the chelation process, the separation of o-GQDs’ photoexcited electron hole pairs leads to their rapid electron transfer to Al3+, in turn leading to the occurrence of a fluorescence-quenching phenomenon. In addition, there was a good linear relationship between the concentration of the Al3+ ions and the fluorescence intensity, and the correlation coefficient of the linear regression equation was 0.9937. This illustrates the potential for the wide application of GQDs in sensing systems, while also demonstrating that Al3+ sensors can be used to detect Al3+ ions.